Invisible-touch model: an integrative framework for postmerger integration - Yang, Monsol Zhengyin (2020)
There is limited research into the postmerger integration (PMI) process in cross-border mergers and acquisitions (CM&As) conducted by emerging-market multinational enterprises (EMNEs) in advanced economies. Although prior studies shed some light on the integration model adopted by EMNEs, the general pattern and process mechanisms of effective integration models remain unclear, which is in stark contrast with the ever-growing trend of EMNEs surging into developed countries via CM&As. What is the effective PMI model adopted by Chinese multinational enterprises in their CM&As in advanced countries? Hence, through the method of longitudinal and in-depth case study for theory building, this thesis seeks to explore the core characteristics, procedural mechanisms, and evolutionary pattern of the successful integration model adopted by Chinese multinational firms. The specific cases are chosen via the theoretical sampling method among major Chinese multinationals from the manufacturing industry that have effectively gone through the whole process of PMI for their CM&As in developed countries. The key contributions of this research are to develop an invisible-touch model and identify its core characteristics, process mechanisms, and evolutionary pattern. In Case Study One, we find that the primary characteristics of the invisible-touch model include surface-level inactive action and deep-level unity-in-diversity for the overall harmonious symbiosis. We hold that the distinction and complementarity between China and the West as a duality is one of the critical prerequisites for the success of the invisible-touch model, and integration governance capacity is the key to harnessing differences and complementarities. In Case Study Two, we identify that the appropriate leverage of conflicting yet complementary forces is imperative for value co-creation and co-capture in the context of CM&As. This is framed as the fundamental mechanism of invisible-touch model, as inspired by the perspective of Yin-Yang balancing as the core of traditional Chinese philosophies for the great insight of maintaining a healthy tension between independence and interdependence, and conflicting yet complementary forces. In Case Study Three, we investigate the evolutionary pattern of the invisible-touch model in serial CM&As. From the perspective of dynamic capabilities, we discover that the invisible-touch model will evolve overtime in both strategic and tactical CM&As, but no fundamental shifts have ever occurred. Hence, the invisible-touch model can be viewed as a long-term strategy for CM&As where the significant diversity in environmental conditions can induce new opportunities for potential contributions to international business research in the era of new globalisation. Overall, our main contribution is to propose an integrative PMI model from a holistic, dynamic, and duality-based perspective, which supplements the existing literature on the integration process of CM&As by EMNEs and extends research about M&As in the international business field. Moreover, we introduce several new concepts, such as, integration governance capacity, value co-creation and co-capture, and exploratory and exploitative dynamic capabilities, among others, into this research project, thus providing new insights into the research into PMI process, integration model, absorptive capacity, and cultural integration. The results of this thesis will broaden the understanding of international business in general, and the knowledge about PMI model for EMNEs in particular. This research also has substantial implications for managerial practices.